(untitled) (Journal of Bangladesh Academy of Sciences, 2023)
We study doubly nonlinear parabolic equation with sign changing solutions. We establish the Hölder regularity of the singular parabolic equations within a parabolic domain. J. Bangladesh Acad. Sci. 47(2); 241-248: December 2023